Self-medication among the elderly and the importance of the pharmaceutical professional: Literature review (Research, Society and Development, 2022)
Self-medication in the elderly becomes increasingly complex due to advanced age and the health condition that this patient is in. Designated by the use of drugs to treat symptoms or diseases without the prescription of a properly trained health professional. It is a reality in Brazilian society and also a problem in public health, as it can cause damage to the health of citizens, and can lead to their death. The practice of inappropriate self-medication can lead to negative consequences, such as: iatrogenic diseases, and masking of evolutionary diseases. The elderly, perhaps for the reason that they are the ones who suffer the most from diseases, are the ones who use a greater amount of over-the-counter medications. They consume an average of two to five drugs daily, being the most fragile to adverse effects and drug interactions. Thus, becoming the most apt to self-medication. The present study aims to highlight the risk factors that are related to the irrational use of medicines in the elderly, and the importance of pharmaceutical care in the face of this act. This is a narrative literature review, of a descriptive and exploratory nature, carried out through the search through the references of the articles. A literature review is, in general, a review of research and discussions by other authors on the topic. The research shows the way in which the elderly use their medicines, demonstrating the dangers that self-medication brings, and the importance of the pharmacist in the face of the correct use of medicines.